Konsep Fasād fī al-Arḍ dalam Perspektif Tafsir Al-Azhar Karya Hamka: Analisis Kerusakan Lingkungan - Sari, Aulia Permata; Adenan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The increasing environmental crisis shows that ecological degradation is not only a technical problem but also reflects a moral and spiritual crisis in human life. The Qur’an, through the concept of fasād fī al-arḍ, warns against human actions that disturb the balance of the earth. This study aims to analyze the meaning of fasād fī al-arḍ in Hamka’s Tafsir Al-Azhar and its relevance to contemporary environmental degradation. This research applies a qualitative approach using library research. The primary sources are Qur’anic verses related to fasād, particularly QS. Ar-Rūm: 41, and Tafsir Al-Azhar, while secondary sources include books, journal articles, and relevant literature on Islamic environmental ethics. The findings reveal that Hamka interprets fasād fī al-arḍ not only as moral and social damage but also as ecological destruction caused by excessive human behavior, such as pollution, exploitation of natural resources, and deforestation. The implication of this study emphasizes the need for spiritual awareness, human responsibility as khalīfah, and environmental ethics in responding to the modern ecological crisis